Social Learning Theory dan Status Merokok Pelajar SMP Negeri - Ansyari, Alya Putri; Rohmah, Nur; Permana, Lies; Nurrachmawati, Annissa; Agustini, Rina Tri (UI Scholars Hub, 2025)
Background. The prevalence of adolescent smokers aged 10–18 in Indonesia increased from 7.2% in 2013 to 9.1% in 2018. Approximately 70 million people in the country are active smokers, with 7.4% of them aged 10–18 years. Aim. This study aims to investigate the association between knowledge, attitude and subjective norms with smoking status among students at a public junior high school in Samarinda. Method. This study uses a cross-sectional design with a quantitative approach. A total of 159 respondents were randomly selected using proportionate stratified random sampling. Data were collected through interviews using a structured questionnaire and analyzed using the contingency coefficient correlation test. Result. A total of 23.9% respondents were identified as smokers, comprising 78.9% males and 21.8% female. Most had high knowledge levels (58.5%), positive attitude toward non-smoking behavior (57.2%), and supportive subjective norms (63.8%). Bivariate revealed statistically significant associations between smoking status and both attitude and subjective norms, while knowledge showed no significant association. The study recommends strengthening anti-smoking education, reinforcing family and school roles, and promoting sustained cross-sectoral collaboration.